Analysing the Settlement of Banking Bad Debts through Cession (Transfer of Receivables Mechanism) - Effendy, Edrick Edwardina; Dasuki, Donny Rustriyandi (Sekolah Tinggi Ilmu Kepolisian, 2025)
Bad debts in banks can arise from debtor negligence, lack of good faith, or incompetence. These bad debts negatively impact a bank’s performance and require immediate resolution. One effective method to address them is by selling or transferring receivables through a legal process known as cession. In this process, a bank (as the original creditor) transfers its claim or credit receivable to another party (the new creditor). As a result, the rights and obligations of the original creditor shift to the new one. This study uses a normative legal approach, focusing on how banks can resolve bad debts through cession. Legally, the transfer of receivables changes the relationship between the debtor and creditor. Cession can be an effective solution for banks, especially when facing legal challenges in executing mortgage right auctions. It offers a faster and simpler legal route, with lower legal risks if proper risk mitigation is in place. To protect creditors legally, risk mitigation should be conducted beforehand. This includes financial risk assessments, ensuring all collateral is properly signed and registered, and notifying debtors of the receivables transfer. With these precautions, the cession mechanism can serve as a strategic and legally sound approach to resolving bad debts.